Urgentni obposteljni ultrazvok (University of Maribor Press, 2023)
Emergency Point-of-care Ultrasound: A Handbook for Medical Students and Interns. This e-book aims to help all young doctors to familiarize themselves with the basic ultrasound examination techniques that together constitute the RUSH (Rapid Ultrasound for Shock and Hypotensian) protocol. The acquired knowledge and skills will be of great help in examining a patient in an emergency department. The basic use of Point-of-care Ultrasound is presented for examination of each individual organ system (lungs, heart, vascular system and abdomen), along with the physical basics of ultrasound and the importance of critical evaluation of ultrasound findings. In each chapter, for better visual representation, the text is accompanied by many illustrative ultrasound images, graphics and animations.